CONTRIBUTIONS OF INTERNATIONAL ACADEMIC MOBILITY HELD IN AUSTRALIA FOR THE TRAINING OF NURSES IN BRAZIL. - Sabina Stieven, Ariane; Oliveira Friestino, Jane Kelly; Barros de Souza, Jeane; Soares Fonsêca, Graciela; Claudino da Silva Filho, Cláudio; Maestri, Eleine (Revista Baiana de Enfermagem, 2022)
Objective: to identify the contributions of international academic mobility, carried out in Australia, to the training of nurses in Brazil. Method: exploratory study with qualitative approach, conducted with eight former exchange students of the Science Without Borders program. The analysis was made by the proposal of the Collective Subject Discourse. Results: the experience offered (ex)exchange students a range of opportunities and exchange of experiences for nursing education. The rich experience in studying subjects in Australia was pointed out, comparing the Problem Based Learning methodology with the traditional methodology experienced in Brazil and highlighting its positive effects. The exchange provided the development of technical-scientific and interpersonal skills, experiences of comparing health systems, in addition to improving language skills and building an ethical-political-social commitment and future professional perspectives. Final considerations: international academic mobility contributed positively to the training of Brazilian nurses, with evidence of personal and professional development.